2013
DOI: 10.1080/00423114.2013.843713
|View full text |Cite
|
Sign up to set email alerts
|

Roll stabilisation of road vehicles using a variable stiffness suspension system

Abstract: A variable stiffness architecture is used in the suspension system to counteract the body roll moment, thereby enhancing the roll stability of the vehicle. The variation of stiffness concept uses the 'reciprocal actuation' to effectively transfer energy between a vertical traditional strut and a horizontal oscillating control mass, thereby improving the energy dissipation of the overall suspension. The lateral dynamics of the system is developed using a bicycle model. The accompanying roll dynamics are also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Braghin et al [9] proposed a rollover control strategy based on aerodynamic load estimation. Anubi et al [10] used variable stiffness suspension to resist vehicle lateral overturning moment. Zhu et al [11] used differential braking and synovial membrane control to control rollover of heavy vehicles, which can effectively improve rollover and yaw stability of heavy vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Braghin et al [9] proposed a rollover control strategy based on aerodynamic load estimation. Anubi et al [10] used variable stiffness suspension to resist vehicle lateral overturning moment. Zhu et al [11] used differential braking and synovial membrane control to control rollover of heavy vehicles, which can effectively improve rollover and yaw stability of heavy vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…When the deformation of the left and right suspensions is not the same, the torsion of bar produces a roll moment opposite to the roll direction of the vehicle body, which reduces the roll angle of the vehicle and achieves the purpose of stabilizer the body. Research shows that many rollover accidents are caused by poor dynamic performance of vehicles (Anubi and Crane Iii, 2013; Li, Yuan, Zhao and Wang, 2018; Li, Ye and Zhang, 2018; Li, Liu, Wang and Wang, 2018). Because of the complexity of driving conditions, the stabilizer bar will often be under the cyclic impact of pavement loads, and even be severely impacted by larger loads.…”
Section: Introductionmentioning
confidence: 99%
“…Most semi‐active suspension systems are designed to only vary the damping coefficient of the shock absorber while keeping the stiffness constant. Meanwhile, in suspension optimization, both the damping coefficient and the spring rate of the suspension elements are usually used as optimization arguments . Anubi et al .…”
Section: Introductionmentioning
confidence: 99%
“…Anubi et al . suggested that a semi‐active suspension system that varies both the stiffness and damping of the suspension element could provide more flexibility in balancing competing design objectives . Only few pieces of work regarding the semi‐active suspension with the variation of suspension stiffness can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation